African Migrant Women’s Understanding and Construction of Sexuality in Australia - Dune, Tinashe (Advances in Social Sciences Research Journal, 2015)
This paper presents findings from an exploratory study that explored how Shona-Zimbabwean women living permanently in Australia understand and construct sexuality in following migration. Main concepts within sexuality under scrutiny in this paper therefore include: gender, embodiment and intimacy. A core finding of the study presented in this paper is how the Shona-Zimbabwean women primarily constructed sexuality in the framework of gender (womanhood) and thus understood both concepts synonymously. The women perceived that the body and intercourse were culturally constructed as means for procreation only. Intimacy and intercourse for relationship-building were perceived to be Western concepts but became a welcome addition to the migrant women’s constructions of sexuality post-migration. This project was informed by feminist methodology and collected data using in-depth, semi-structured focus groups in Adelaide, South Australia from fourteen women aged 29 to 53 years, across four focus groups. A significant contribution of this research is that a better understanding of how sexuality is understood across cultures highlights the relevance, or lack thereof, of Western concepts of sexuality for ageing (African) women. It also brings to question the appropriateness of current policy, service delivery and health promotion in regards to sexual wellbeing in a contemporary and multi-cultural Australia.